Performance of an extrapolation chamber in computed tomography standard beams (Brazilian Journal of Radiation Sciences, 2021)
Among the medical uses of ionizing radiations, the computed tomography (CT) diagnostic exams are responsible for the highest dose values to the patients. The dosimetry procedure in CT scanner beams makes use of pencil ionization chambers with sensitive volume lengths of 10 cm. The aim of its calibration is to compare the values that are obtained with the instrument to be calibrated and a standard reference system. However, there is no primary standard system for this kind of radiation beam. Therefore, an extrapolation ionization chamber, built at the Calibration Laboratory (LCI), was used to establish a CT primary standard. The objective of this work was to perform some characterization tests (short- and medium-term stabilities, saturation curve, polarity effect and ion collection efficiency) in the standard X-ray beams established for computed tomography at the LCI.
Keywords: Extrapolation chamber; computed tomography; dosimetry.